RAT Association’s Structure: Measuring Fluency and Flexibility of Thinking - V.K. Lukianova (Экспериментальная психология)
The Remote Association Test (RAT) or Mednick's task is used to assess creative thinking and investigate insight. Despite various modifications of RAT (CRAT, fRAT, vRAT, LI-RAT) and their adaptations in different languages, the problem of heterogeneity of the association structure remains unsolved. The purpose of this paper is to analyze papers devoted to association structure heterogeneity and its impact on RAT solutions. A review of articles from 2019-2023 highlights the following causes of association structure heterogeneity: semantic memory features, linguistic features, associative structure and strengths, and task solution space. As a result, the homogeneity of association structure in RAT is more often associated with fluency, while heterogeneity is more often associated with flexibility. At the same time, both factors, being indicators of divergent thinking, are laid down in RAT modifications. However, recent articles predominantly emphasize fluency estimation. Only considering RAT through problem-solving space makes it possible to control the fluency factor. The conclusion is that RAT, combining divergent and convergent stages, in a certain sense restores the unity of creative and critical thinking.